Orthodontics and you: patient information booklet - Tan, Lawrence; Abu Bakar, Noraini (IIUM Press, 2016)
Orthodontic treatment is becoming increasingly popular. Having straight teeth, and a nice smile, is seen as one of the key to a better quality of life.